The influence of carotid atherosclerosis on surgical outcomes of patients with cervical spondylotic myelopathy: A retrospective study. Issue 5 (4th February 2022) - Li, Bohan; Liu, Shuling; Wang, Yongmei; Zhao, Jie; Song, Yang; Xu, Wen; Zhang, Cheng; Gao, Chunzheng; Zhao, Qian; Wu, Dongjin
Abstract : Abstract: The appearance of atherosclerosis in the carotid artery may be suggest the possibility of atherosclerosis in the spinal cord artery, which can cause spinal cord ischemia and further lead to neural element damage. According to the inclusion and exclude standard, there are 137 patients with cervical spondylotic myelopathy (CSM) incorporating retrospective analysis. These patients were consecutively admitted into The Second Hospital- Cheeloo College of Medicine-Shandong University from January 2016 to December 2018 and have accepted surgical treatment. All patients were examined by color Doppler ultrasound to detect carotid atherosclerosis before surgery. All patients were divided into 2 groups according to the presence or absence of carotid atherosclerosis: carotid atherosclerosis group (n = 88) and noncarotid atherosclerosis group (n = 49). All patients were followed up for at least 12 months after surgery. Demographic and surgery-related data were collected and analyzed to identify potential factors that affect the surgical outcomes in CSM. The average age of carotid atherosclerosis group (51 males and 37 females), and noncarotid atherosclerosis group (24 males and 25 females) were 62.02 ± 10.34 years (range, 38–85 years) and 49.61 ± 10.28 years (range, 26–67 years), respectively. In carotid atherosclerosis group: pre and postoperative modify Japanese Orthopedic Association Scores (mJOA score) were 11.58 ± 1.82 and 14.36 ± 1.64; the recovery rate of mJOA score was 45.57% ± 13.28%. In noncarotid atherosclerosis group: pre and postoperative mJOA score were 12.00 ± 2.11 and 15.04 ± 1.70; the recovery rate of mJOA score was 53.90% ± 13.22%. Univariate logistic regression analysis demonstrated that gender ( P = .004), age ≥65 years ( P = .001), duration of symptoms ≥12 months ( P = .040), smoking history ( P < .001), preoperative mJOA score ≤11 ( P = .007) and carotid atherosclerosis ( P = .004) were related to poor surgical outcomes. Multivariate logistic regression analysis showed significant correlations between poor surgical outcomes and age ≥65 years ( P = .047), smoking history ( P = .010), preoperative mJOA score ≤11 ( P = .008) or carotid atherosclerosis ( P = .047). Carotid atherosclerosis may be a risk factor for poor surgical outcomes in CSM.